INCREASING NUTRITIONAL VALUE OF CHOPPED MEAT SEMI-FINISHED PRODUCTS BY ADDING SEEDS QUINOA - Sokolova E.B. (Uman National University of Horticulture, 2021)
The articles tudy the process of increasing the nutritional and biological value of minced meat semi-finished products. The directions of improving the quality of minced semi-finished meat products based on vegetable origin additives are considered. One of the promising biologically active substances is the culture of quinoa. Quinoa fruit contains an average of 16-20% protein. The high protein value is due to the content of histidine, isoleucine, leucine, phenylalanine, thre onine, tryptophan, valine and, mainly, lysine and methionine, essential amino acids. Quinoa seeds are also rich of microelements (K, Ca, P, Mn, Zn, Cu, Fe and Na) and vitamins C and E. A technology of minced semi-finished meat products with a partial replacement of wheat bread by quinoa seeds flour has been proposed. Organoleptic studies research found that increase of quinoa seeds flour mass in the productcomposition will lead to color, consistency and taste change significantly. As a result of the study, it was found that the adding of quinoa seeds flour in the proportion of 8% out of total mass to minced meat gives the product a nutty flavor, and due to the small amount of bread, the cutlets have a porous and juicy consistency. Quinoa seed meal significantly changes the nutritional and biological value of the finished product. In products made according to the new recipe, the amount of protein increases from 11.77 to 12.25% compared to the control. It was found that the quinoa seed flour in the composition of minced semi-finished meat products does not affect the pH and overall acidity of the product. It was determined that increase ofsuch flour in the samples lead to decrease the moisture in total mass fraction. The higher the content of quinoa seeds flour in the semi-finished product, the higherlevel of compactnessconsistency of the finished product is, since the content of free moisture is significantly reduced. Therefore, to use such type of additive as a complete substitute for wheat bread, it is necessary to adjust the amount of moisture added to the minced meat according to the recipe. The advantages of the developed minced semi-finished meat products with quinoa seed flour in comparison with traditional cutlet masses in terms of nutritional and biological value have been proven. The developed product will expand the range of targeted products with a controlled composition of proteins, fats, carbohydrates, vitamins and other biologically active substances.